PEMBINAAN DAN PENDAMPINGAN KELOMPOK PENDUKUNG ASI (KP ASI) “BINTANG BERPASANG SIRIH ADAT” DALAM UPAYA PENCEGAHAN STUNTING - Alyensi, Fatiyani; Laila, Ani; Hevrialni, Rully (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2022)
The World Health Organization (WHO) in 2009 and the American Academy of Pediatrics (AAP) in 2012 recommended optimal nutrition for newborns, namely the global strategy of exclusive breastfeeding for 6 months. Mother's milk (ASI) is the liquid of life created by God specifically for babies that contains white blood cells, immune substances, enzymes, hormones and proteins that are suitable for babies (Kemenkes, 2013). Breast milk is the best food for babies at the beginning of their life. Breast milk is proven to have advantages that cannot be replaced by any food and drink because breast milk contains the most appropriate and complete nutrients for the growth and development of babies (Sugiarti, et al 2011). The purpose of the activity is to provide assistance and guidance to KP ASI mothers. The target audience is 11 KP ASI mothers in RW 2 with the method of reviewing materials and skills, providing assistance and coaching and evaluation. Time and place of activities from February – August 2021 at Posyandu and nursing mothers' homes. The output is IPR and a practical guide for ASI Support Groups. There is an increase in knowledge of KP ASI mothers on Early Breastfeeding Initiation (IMD) materials from an average of 70 to 90 and breastfeeding materials from an average of 80 to 90. solve problems with mothers. Therefore, there is a need for coordination from the Rejosari Health Center, especially the coordinating midwife in every breastfeeding support group activity so that the program can run smoothly and be implemented optimally, especially in RW 2, Sialang Sakti Village. Keywords: Coaching, Mentoring, KP ASI